Gather in the metaverse: Learning outcomes, virtual presence, and perceptions of high- and low-achieving pre-service teachers of English as a Foreign Language - Chen, Hsieh-Jun (Education and information technologies, 2024)
Despite the widespread integration of technological tools in pre-service English-as-a-Foreign-Language (EFL) education, there has been a dearth of research investigating the effects of the latest virtual platforms on pre-service teachers' competence in lesson planning, perceived presence, and perceptions, particularly in relation to high- and low-achieving pre-service teachers. This study, accordingly, investigated the potential benefits of utilizing innovative online learning platforms, specifically Gather, in teacher preparation education. Through a mixed-methods, quasi-experimental, within-subjects design, 46 English-major junior students enrolled in a pre-service EFL course at a private university in central Taiwan were assigned two lesson planning tasks, the first involving in-class discussion and the second utilizing Gather for interaction. Based on their performance in the first task, the students were divided into two groups: high achievers and low achievers, each comprising 23 students. Analysis of their performances, responses to the Multiple Presence Scale, and reflective journals indicated that both groups demonstrated improvement in lesson planning and reported positive experiences in the virtual learning environment, particularly in terms of physical presence, social presence, and self-presence. Moreover, the students expressed a preference for online learning facilitated by Gather. Notably, while both groups acknowledged the perceived presences in Gather, high achievers exhibited significantly higher levels in all three aspects of presence, suggesting a stronger sense of immersion in the virtual learning setting, akin to face-to-face classroom meetings. These results suggest that platforms like Gather can enhance lesson planning outcomes, foster engagement, and serve as a valuable alternative to traditional videoconferencing tools in teacher preparation education.